2019
DOI: 10.1021/acs.inorgchem.9b00924
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Spectroscopic Behaviors of a Novel Ruthenium(II) Complex with a Six-Membered Chelate Structure

Abstract: A novel polypyridyl ruthenium(II) complex with a sixmembered chelate ring ([Ru(dmb) 2 (8pyq)] 2+ ) was designed and synthesized. The oxidation potential was shifted to the negative potential direction, and relatively intense metal-to-ligand charge transfer absorption in the longerwavelength region was observed for [Ru(dmb) 2 (8pyq)] 2+ compared with the reference complexes without any six-membered chelate rings. The electrochemical and spectroscopic properties of [Ru(dmb) 2 (8pyq)] 2+ were discussed in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In comparison, the oxidation process of the Ru II /Ru III couple occurs at a slightly more positive potential than that of the Os II /Os III couple, as the occupied dπ orbitals of Os(II) have a higher energy than those of Ru(II) [2g,9] . The first two reduction processes of all acquired complexes are shifted to positive potentials compared with those of the reference compounds because the presence of the terpyridine units in the bridging ligands significantly stabilizes the ligand π* orbitals [10] . The presence of one oxidation process for two peripheral terpyridine moieties in the trimetallic complexes indicates that the two terpyridine coordination sites have equal energies in the coordination systems.…”
Section: Resultsmentioning
confidence: 96%
“…In comparison, the oxidation process of the Ru II /Ru III couple occurs at a slightly more positive potential than that of the Os II /Os III couple, as the occupied dπ orbitals of Os(II) have a higher energy than those of Ru(II) [2g,9] . The first two reduction processes of all acquired complexes are shifted to positive potentials compared with those of the reference compounds because the presence of the terpyridine units in the bridging ligands significantly stabilizes the ligand π* orbitals [10] . The presence of one oxidation process for two peripheral terpyridine moieties in the trimetallic complexes indicates that the two terpyridine coordination sites have equal energies in the coordination systems.…”
Section: Resultsmentioning
confidence: 96%
“…As shown in Figure a, mononuclear complexes shown a unique reversible oxidation half-wave in the anodic potential region which is ascribed to the oxidation of the Ru­(II) to Ru­(III) (see Δ E in Table ). In the cathodic region, several reversible and irreversible reduction half-wave at −1.2 to −1.6 V were observed, which can be assigned to the one-electron reduction processes localized on polypyridyl ligands . The reversible redox processes suggest the high stability of complexes under the operation conditions applied in LEC devices owing to the reversible nature of the red/ox processes …”
Section: Resultsmentioning
confidence: 94%
“…Obviously, all binuclear complexes exhibited a reversible oxidation peak in the anodic potential region which is ascribed to the oxidation of Ru(II) to Ru(III). 72 Furthermore, the complexes undergo an irreversible oxidation at 1.87 V, which can be attributed to the oxidation of the phenanthroimidazole ligand, as it can be seen in the CV of the ligand (Fig. 2).…”
Section: Electrochemical Characterizationmentioning
confidence: 83%
“…As described previously for similar complexes, the first and second reduction processes are observed on the phenanthroimidazole and bipyridine ligands, respectively. [72][73][74] Comparison of the integrated area under the oxidation and reduction peaks of the differential pulse voltammogram (DPV) for D1 with one-electron oxidation couple of ferrocene showed that the binuclear complex underwent quasi-reversible and reversible two-electron oxidation and reduction processes (Fig. S16, ESI †).…”
Section: Dalton Transactions Papermentioning
confidence: 99%